Planned Early Delivery or Expectant Management for Late Preterm Preeclampsia (PHOENIX): A Randomized Controlled Trial. Issue 3 (September 2020) - Chappell, L.C.; Brocklehurst, P.; Green, M.E.; Hunter, R.; Hardy, P.; Juszczak, E.; Linsell, L.; Chiocchia, V.; Greenland, M.; Placzek, A.; Townend, J.; Marlow, N.; et al.
Abstract : ( Lancet . 2019;394:1181–1190) Preeclampsia occurs in 2% to 3% of pregnant women and is associated with substantial maternal and neonatal morbidity and mortality. Prompt delivery is the recommended management for preeclamptic women after 37 weeks' gestation, as this will decrease the risk of maternal complications while minimally affecting risk to the neonate at this gestational age. However, it is unclear what the best management strategy is for women who develop preeclampsia between 34 and 37 weeks' gestation. In these cases, complications related to expectant management (EM), such as stillbirth or worsening fetal growth restriction and increased maternal morbidity associated with continuing the pregnancy, must be weighed against the neonatal complications associated with early delivery (infant immaturity). Current guidelines in the UK recommend EM until 37 weeks' gestation, with earlier delivery if severe preeclampsia or other complications arise. This study from the UK compared earlier initiation of delivery with EM in women diagnosed with preeclampsia between 34 and <37 weeks gestation.